The protective effect of curcumin against lithium-induced nephrotoxicity in rats - Mohammad Shaterpour; Fatemeh Shaki; Maryam Ghasemi; Majid Jafari-Sabet; Ali Ziar; Ramin Ataee (Mazandaran University of Medical Sciences, 2017)
Lithium is an element which has been used as salts of chloride or carbonate for many years in the treatment of some psychological disorders such as mania, bipolar or schizophrenic diseases. Chronic application of lithium may induce some serious nephropathies such as natriuresis, renal tubular acidosis, tubulointerstitial nephritis progression to progressive chronic kidney disease and hypercalcemia and, most commonly, nephrogenic diabetes insipidus. Curcumin is an antioxidant derived from Curcuma longa (turmeric or curcuma) which has the ability to react directly with reactive species and up-regulation of many cytoprotective and antioxidant proteins. The preventive roles of curcumin in nephropathies were reported, but there was little information on the protective effect of curcumin against lithium-induced nephrotoxicity. In this study, male Wistar rats divided into five groups of six each and were treated as follows: group1; animals were received lithium chloride as 2 mmol/kg, group 2; animals were received normal saline (0, 5%), group 3; animals were received curcumin (200 mg/kg), group 4 animals were received curcumin plus lithium and group 5; animals were received solvent intraperitoneally for three weeks. Then the animals were killed and biochemical parameters of blood were assayed and histopathological assessment was performed. The results have shown that curcumin significantly improved the biochemicals (BUN, creatinine, malondialdehyde). Curcumin prevented significantly the histological parameters that were changed by lithium administration in rats. Our results provide new insights into beneficial usages of curcumin in chronic nephrotoxicity induced by lithium salts.